Relationship between Onodera׳s Prognostic Nutritional Index and Subpopulation Lymphocyte Counts in Hemodialysis and Peritoneal Dialysis Patients - Gyoung-Hoon Kang; Ga In Yu; Ye Na Kim; Ho Sik Shin; Yeon Soon Jung; Hark Rim; Hyun Yul Rhew (The Korean Society of Nephrology, 2014)
No standard method for assessing the nutritional status in dialysis patients. In the present study, we undertook an evaluation to determine whether estimation of geriatric nutritional risk index (GNRI) and lymphocyte subset counts can be helpful in diagnosis of malnutrition in hemodialysis (HD) and continuous ambulatory peritoneal dialysis (CAPD) patients. Methods: We examined the GNRI and lymphocyte subset counts of 50 HD patients (55.8±12.7 years; 28 men and 22 women) and 16 CAPD patients (49.8±14.5 years; 10 men and 6 women). The GNRI is calculated based on the serum albumin level and total lymphocyte count and uses the following equation: GNRI=[14.89×albumin (g/dL)]+ [41.7×(weight/ideal body weight)]. Logistic regression analysis was performed for predicting malnutrition in dialysis patients. Results: The average GNRI value was 100.1±8.4 in HD patients and 99.2±8.1, and GNRI values were normally distributed. lymphocyte subset counts were not different between HD patients and CAPD patients. Lymphocyte subset counts were lower in patients with higher GNRI (GNRI ≥100). According to logistic regression for predicting malnutrition according to GNRI, age, female and CD 19 count predicted malnutrition in hemodialysis and peritoneal dialysis patients Conclusions: These results suggest that GNRI and lymphocyte subset counts (especially CD 19 count) may be a significant nutritional marker in HD and CAPD patients.